2016
DOI: 10.1142/s1088424616500528
|View full text |Cite
|
Sign up to set email alerts
|

A hindered subphthalocyanine that forms crystals with included aromatic solvent but will not play ball with C60

Abstract: A novel subphthalocyanine containing bulky substituents placed at its peripheral sites (i.e. 2,3,9,10,16,17-hexa(2′,6′-di-iso-propylphenoxy)boron subphthalocyanine) was prepared and assessed for supramolecular binding with C[Formula: see text], through crystallisation and fluorescence studies. Three different crystal polymorphs of the subphthalocyanine were obtained that showed inclusion of a single aromatic solvent molecule within the well-defined cavity of the molecule but complete exclusion of C[Formula: se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…20 A similar effect was detected in the low-temperature NMR spectrum of a SubPc peripherally substituted with six 2′,6′-di-iso-propylphenoxy moieties. 19 In the case of SubPc π-complexes featuring a Cp*Ru + unit coordinated to either the concave or the convex face of the macrocycle ( 63–66 , Fig. 12), a notable diatropic effect on the Cp* moiety was observed in the case of the endo -coordinated compound, while an exceptionally small shift was detected for the exo -coordinated complex.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
See 2 more Smart Citations
“…20 A similar effect was detected in the low-temperature NMR spectrum of a SubPc peripherally substituted with six 2′,6′-di-iso-propylphenoxy moieties. 19 In the case of SubPc π-complexes featuring a Cp*Ru + unit coordinated to either the concave or the convex face of the macrocycle ( 63–66 , Fig. 12), a notable diatropic effect on the Cp* moiety was observed in the case of the endo -coordinated compound, while an exceptionally small shift was detected for the exo -coordinated complex.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
“…chlorobenzene, 13 o -dichlorobenzene, 14,15 or 1-chloronaphthalene 16 ). 11 SubPcs synthesis has also been carried out by addition of a 1 M solution of BCl 3 in heptanes 17–19 or dichloromethane 20–27 to a solution of the starting phthalonitrile in a high-boiling solvent such as p -xylene, 22,24 1-chloronaphthalene, 18 o -dichlorobenzene, 17,19,21,23,25,26 1,2,4-trichlorobenzene 20 or dimethyl sulfoxide. 11,27 Microwave irradiation has also been employed for SubPc preparation.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concave π‐surface space in SubPcs should be useful for trapping small arene compounds and the resulting clathrates should be suitable for X‐ray crystallographic analysis. During our research in this direction, McKeown and co‐workers observed that hexa(2′,6′‐diisopropylphenoxy)boron SubPc forms crystals that included an aromatic solvent . We herein disclose the X‐ray crystallographic analysis of a series of clathrates of trifluoroethoxy‐coated SubPcs; we found that they routinely contain one small arene at the center of the concave cavity.…”
Section: Figurementioning
confidence: 99%
“…[a] S. Mori, J. Wang, E. Tokunaga, Prof. N. Shibata Department of Nanopharmaceutical Sciences NagoyaInstitute of Technology Gokiso, Showa-ku, Nagoya4 66-8555 (Japan) E-mail:nozshiba@nitech.ac.jp SubPc forms crystalst hat included an aromatic solvent. [7] We herein disclose the X-ray crystallographic analysis of as eries of clathrates of trifluoroethoxy-coated SubPcs;w ef ound that they routinely contain one small arene at the center of the concavec avity. The trifluoroethoxy moiety plays an important role in the formation of arene clathrates, as revealed by ac omparative study using nonsubstituted SubPc.…”
mentioning
confidence: 96%